Improved SMC cardinality-balanced multi-Bernoulli forwardbackward smoothing track-before-detect algorithm - Jiazheng PEI; Yong HUANG; Yunlong DONG; Xiaolong CHEN (Tongxin xuebao)
For the tracking problem of multiple maneuvering targets in radar observation,the sequential Monte-Carlo cardinality-balanced multi-Bernoulli track-before-detect (SMC-CBMeMBer-TBD) algorithm is inaccurate in the estimation of the number of targets and the precision of state estimation.An improved algorithm based on SMC-CBMeMBer forward backward smoothing track-before-detect algorithm was proposed.In the algorithm,the multi target particle swarm optimization (MOPSO) was added between the process of prediction and update,and the fitness function was set up based on the observation value to make the particle set move to the position of the larger posterior probability density distribution,and solve the particle poverty in the heavy sampling process.In the update step,the algorithm was used.Then the smoothing recursive method was added,and the arithmetic operation time was prolonged,but the number and the state estimation precision were improved.The simulation results show that compared with the CBMeMBer-TBD method,the proposed algorithm improves the accuracy of the estimation of the number of maneuvering targets and the accuracy of the target state estimation.